Estimation of ultra-stability of methane hydrate at 1 atm by thermal conductivity measurement (2010)
Thermal conductivity of methane hydrate was measured in hydrate dissociation self-preservation zone by means of the transient plane source (TPS) technique developed by Gustafsson. The sample was formed from 99.9% (volume ratio) methane gas with 280 ppm sodium dodecyl sulfate (SDS) solution under 6.6 MPa and 273.15 K. The methane hydrate sample was taken out of the cell and moved into a low temperature chamber when the conversion ratio of water was more than 90%. In order to measure the thermal conductivity, the sample was compacted into two columnar parts by compact tool at 268.15 K. The measurements are carried out in the temperature ranging from 263.15 K to 271.15 K at atmospheric pressure. Additionally, the relationship between thermal conductivity and time is also investigated at 263.15 K and 268.15 K, respectively. In 24 h, thermal conductivity increases only 5.45% at 268.15 K, but thermal conductivity increases 196.29% at 263.15 K. Methane hydrates exhibit only minimal decomposition at 1 atm and the temperature ranging from 263.15 K to 271.15K. At 1 atm and 268.15 K, the total gas that evolved after 24 h was amounted to less than 0.71% of the originally stored gas, and this ultra-stability was maintained if the test was lasted for more than two hundreds hours before terminating.